Leaching kinetics of limonite and nontronite ores. (8th June 2009) - Tang, Jessica; Valix, Marjorie
Bioleaching of nickel laterite ores is the extraction technology based on the use of heterotrophic micro-organisms and their organic acid products to dissolve metals from oxide minerals. This study examined the leaching kinetics of limonite and nontronite ores by metabolites including citric, lactic and malic acids. In addition the roles of acidolysis and complexolysis in the kinetic of metal dissolution were examined. The leaching process was found to follow the chemically controlled model. The roles of acidolysis and complexolysis on the kinetics of leaching were found to depend on the leaching conditions. Acidolysis is the most important under acidic conditions but under weaker acidic conditions the complexolysis become dominant. These results suggest the importance of both acid activity and the nature of complexing agents in dissolving metals such as nickel and cobalt from laterite minerals.